Sistem Informasi Administrasi Keuangan Siswa Berbasis Web Pada SMA Yadika Kota Jambi - Nadia Kurniati, Asri; Devitra, Joni (Jurnal Manajemen Sistem Informasi, 2022)
Jambi City Yadika High School is a special institution to provide educational knowledge to students under the supervision of teachers located in Jambi City, having its address at Jalan Maya, South Lingkar, South Jambi. The process of processing school financial administration often experiences various obstacles. Constraints that often occur include student payments such as Education Development Donations as well as payment of building fees and school financial reporting. The benefits of the research carried out are improving the quality of service to students, managing student financial administration data to be relatively faster and accurate, and student finance administration can be known simply by accessing a web page, without having to come to the administration section. The purpose of the research is to design the Analysis and Design of a Web-Based Student Financial Administration Information System at Yadika High School Jambi City. The method uses a prototype. The results of the research are data processing applications that have been designed to facilitate data processing and report generation. Suggestions before using the application, it is better for the user to get training first so that it can be operated optimally.